Sonography and EMG Biofeedback’s Role in PIN Syndrome After Rehabilitation? A Case Report - Evi Rachmawati Nur Hidayati; Zuliza Adha; Hafizia Asri Yusviani; Savira Widha Alifprilia (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
The radial nerve divides into two terminal branches the superficial radial nerve and the posterior interosseous nerve. Posterior interosseous nerve entrapment is associated with weakness in the extension of fingers, atrophy of the forearm muscles, and localized pain in the lateral aspect of the elbow and proximal forearm without sensory deficits. A 37-year-old man complained of difficulty of right finger extension (MMT 2) and persistent pain (VAS 5) at the forearm after a fall from a motorcycle six months before admission. We treated the patient with a physical rehabilitation program for three months and a total of 12 visits. Sonography and electromyography (EMG) biofeedback were performed to evaluate improvement after the physical rehabilitation program. After three months, the pain was relieved, and forearm extensor muscle strength increased. This showed that sonography and EMG biofeedback play a role in the detection and evaluation of muscle and nerve abnormality due to posterior interosseous nerve (PIN) syndrome.